The 1984 Institute of Texas Studies: The Texas Experience to 1865 An Evaluation - Curran, Linda T.; Holahan, Carole K.; Texas Univ., Austin. Measurement and Evaluation Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Forty-four participants completed a questionnaire (Appendix A) designed to evaluate the Institute of Texas Studies: "The Texas Experience to 1865." Section 1 of the questionnaire consisted of a listing of 20 presentations and activities of the institute and one general institute evaluation item. The remaining sections (2-10) were free-response, with participants being asked to comment on various aspects of the institute, such as format and length, as well as to make recommendations or suggestions for improving future institutes. Also included were questions regarding suggested background reading participants accomplished before and during the institute and questions about their teaching backgrounds and experience. Participant responses to these sections were summarized by grouping similar responses together (Appendix B). On the basis of these groupings, a set of content categories was derived and frequencies per category tallied to summarize the free-response data in a concise manner, as well as one that would facilitate interpretation. The institute received a very favorable evaluation by respondents: most presentations were rated as excellent; and most respondents favored the present institute format. Suggestions to improve the institute were discussed. (PN)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adults; College Faculty; Elementary School Teachers; Elementary Secondary Education; Evaluation Methods; Higher Education; Inservice Teacher Education; Institutes (Training Programs); Program Development; Program Evaluation; Questionnaires; Secondary School Teachers; State History; University of Texas Austin; Institute of Texas Studies; Reports, Research; Tests/Questionnaires.